2020
DOI: 10.1186/s12906-020-2818-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anticandidal potency of Syzygium aromaticum (clove) extracts against vaginal candidiasis

Abstract: Background: Candida vaginitis is a global health hazard that increases morbidity among women of childbearing age. Recent studies have revealed a high incidence of drug-resistant Candida strains. Additionally, treating Candida vulvovaginitis during pregnancy is challenging as antifungal therapy is associated with fetal abnormalities. Hence, it is important to develop novel therapeutic strategies to treat vulvovaginal candidiasis. Methods: In this study, we used the disc diffusion method to evaluate the anticand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 36 publications
0
30
0
1
Order By: Relevance
“…29 The high eugenol content of clove essential oil was the main reason for its antifungal effects. 30,31 In addition, eugenol also had a good inhibitory effect on Sphaceloma ampelinum, Valsa mali, Fusarium graminearum, Ralstonia solanacearum and Rhizopus stolonifer among others. [32][33][34][35] Previous studies have shown that cell membranes may be one target in eugenol's destruction of fungi, because eugenol can increase the permeability of fungal cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…29 The high eugenol content of clove essential oil was the main reason for its antifungal effects. 30,31 In addition, eugenol also had a good inhibitory effect on Sphaceloma ampelinum, Valsa mali, Fusarium graminearum, Ralstonia solanacearum and Rhizopus stolonifer among others. [32][33][34][35] Previous studies have shown that cell membranes may be one target in eugenol's destruction of fungi, because eugenol can increase the permeability of fungal cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The antifungal activity of the CEO may justify this. S. aromaticum has definite antifungal activity against C. Albicans (Mansourian et al, 2014;Yassin et al, 2020). Eugenol has also been reported to reduce adhesion, biofilm formation, and even alter the morphogenesis of C. Albicans (De Paula et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Clove (Syzygium aromaticum) is used for its culinary and medicinal virtues. Since then, other properties have been discovered, such as an anti-inflammatory, antibacterial, and antianaphylactic and anticandidal effect (Adli et al, 2018;Yassin et al, 2020). Thus, the influential role of cloves as inhibitors of various degenerative diseases is attributed to diverse chemical constituents in high concentrations with antioxidant activity (Astuti et al, 2019;Batiha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…e clove extract was reported to contain eugenol (58.8%), eugenyl acetate (23.8%), trans-Caryophyllene (14.4%), and α-Humulene (1.8%). Among all organic extracts of clove, ethyl acetate extract showed the highest inhibitory activity in terms of zone of inhibition against the test species of Candida [32]. e meswak (S. persica) root stick is widely used throughout the Arabian and Muslim world during ablution before every daily prayer as it is highly recommended for oral hygiene by Prophet Mohammad.…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 99%